Utilização de água residuária no desenvolvimento de Moringa oleifera Lam. - Almeida, Gleidiane Nascimento de (Universidade Federal Rural do Semi-Árido, 2018)
The reuse of fish farming effluents for seedlings production has become a viable alternative, besides being economical and important for the preservation of the environment. However, there are not many studies on the reuse of this water and the ones that were carried out are mostly for the production of agricultural crops. Therefore, it is necessary to study the reuse of this water for forest species. Therefore, the objective of this study was to evaluate the use of fish farming water in the production of Moringa oleifera Lam. Seedlings at different concentrations. The wastewater was obtained from a 20 ppm fish tank, located in the aquaculture sector of the Department of Animal Sciences of the Federal University of the Semi-Arid (UFERSA) and diluted with the water supplied by the institution. The treatments used were: 0% - 0.51 dS.m-1 (T1 - control); 25% - 9.0 dS.m-1 (T2); 50% - 15.96 dS.m-1 (T3); 75% - 39.4 dS.m-1 (T 4) and 100% - 53.5 dS.m-1 (T 5). For the developmental evaluation, the seedlings were transplanted in polyethylene bags with five replicates per treatment. The irrigations were performed daily and weekly. The seedlings were evaluated according to the non-destructive variables of the height, collection diameter and number of leaves and of destructive form at the end of the experiment, evaluating the weight of fresh and dry mass of the leaves , stem and root. With the data, biomass allocation to the leaves, stem and root, root / shoot ratio was calculated and the relative and absolute growth rate as well as the Dickson Index were calculated. For height, collection diameter and number of leaves there were reductions from the T3 treatment, the production of fresh and dry matter of the leaves and roots was affected in the treatments T3 and T4 and T5, already for the dry and fresh matter of the stem there was reduction from the T4 treatment of 76.6%, and the T2 treatment presented higher value. For the other variables, the T2 treatment plants presented values similar to the control treatment (T1). According to the results, it was concluded that the concentration of 25% of wastewater from fish ponds with electrical conductivity of 9 dS.m-1 can be used for irrigation of Moringa oleifera seedlings.
Monografia
Keywords: Efluente; Reuso; Produção de mudas; Estresse salino; Eflluent; Reuse; Seedling production; Saline stress; CIENCIAS AGRARIAS::RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL